PENGGUNAAN KAOLIN SEBAGAI BAHAN PENGISI KOMPON LATEKS UNTUK PELAPIS KAIN INTERLINING - Luftinor, Luftinor (Balai Riset dan Standardisasi Industri Palembang, 2018)
A study of the manufacture of natural latex liquid compound as a coating material on the manufacture of hard interlining fabric by varying the fineness of kaolin 100 mesh, 250 mesh and 400 mesh as a filler material plus other chemicals. The purpose of this research is to get the right natural liquid latex compound formula as a coating material in the manufacture of interlining fabrics that have specifications in accordance with the SNI 0894-2008 Standard of Hard Cloth (Interlining). Interlining fabrics are fabrics used to coat certain parts of clothing such as collars, waist, buttons, sleeves, shoulders and other parts that require high stiffness and a stable shape to enhance the appearance of clothing. The study was conducted by varying the fineness of the kaolin filler in 3 treatments each 100 mesh, 250 mesh and 400 mesh and varying the amount of kaolin filler in 4 treatments each 90 g, 180 g, 270 g and 360 g. The parameters tested were fabric rigidity, adhesive power, tensile strength, elongation and tear strength of fabric. Increased fineness of a kaolin filler from 100 mesh to 400 mesh in latex compound as a coating material, the fabric rigidity, adhesion, tensile strength, elongation and tear strength of the fabric tend to increase. Whereas the increasing amount of kaolin filler usage from 90 g to 270 g as a coating material can increase the fabric rag, but the subsequent addition decreases fabric rigidity. Conversely, the weight gain of fillers from 90 g to 360 g decreases the adhesiveness, tensile strength, elongation and tear strength of the fabric. The best results and fulfill the requirements of SNI 0894-2008 were obtained on formula IX using a 90 g kaolin filler and kaolin 400 mesh fineness with fabric stiffness value of 86.2 mg.cm, adhesion 1,8 kg / cm, tensile strength 40,59 kg for direction of warp and 31,43 kg for feed direction, 41.64% for luran direction and 36,63% for feed direction, tear strength 7,12 kg for warp and 6,53 kg for feed direction.